Synthesis and photovoltaic properties of organic molecules based on difluoroquinoxaline derivatives for OPVs. (2nd July 2020) - Kong, MinSung; Lee, Jihoon; Song, Suhee; Lee, Won-Ki; Kim, Jin Young; Park, Sung Heum; Jin, Youngeup
Abstract: We designed and synthesized two novel low band gap small molecule donors (M1 and M2) that consist of benzo[1, 2- b :4, 5- b ′]dithiophene as the electron-rich core and 6, 7-difluoroquinoxaline as the electron-deficient end-group. M1 and M2 with A-D-A type structure were synthesized via Stille coupling reaction for use in OSCs. The absorption maximum of the M1 and M2 in solid thin films exhibited at 536 and 540 nm and absorption onset at 582 and 592 nm, corresponding to band gaps of 2.31 and 2.10 eV, respectively. Although the absorption of the M1 with branched alkyl chain was blue shifted as compared to M2, the branched alkyl chain in benzodithiophene core provide appropriate solubility to provide good OSC performance.